HUBUNGAN ANTARA MEROKOK DENGAN GAMBARAN FUNGSI GINJAL PADA KARYAWAN PT.X - Syamsi, Nur; Tanra, Andi Alfia Muthmainnah; HS, Mariani Rasjid (Universitas Tadulako, 2021)
The chronic kidney disease is a global health problem with increasing prevalence and incidence and a poor prognosis. Therefore, those brought about by risk factors are primarily those which can be modified and controlled for their occurrence. One of the risk factor is smoking habit. The objective of this study was to determine the associations between smoking and renal function profiles in PT.X employees. The study was conducted by using descriptive analytical study with a cross sectional design based on smoking habits and blood test samples of employees. The sample were 40 employees in PT.X which determined by consecutive sampling. The results showed that there were no associations between smoking with age (p = 0.222) and azotemia (p = 1.00) but there were associations between smoking and blood creatinine levels (p = 0.001), urea (p = 0.023), eGFR (p. = 0.001), and the stages of chronic kidney disease (p = 0.047). Based on the study results, in can be concluded that there were associations between smoking and renal function profiles among employees of PT. X